Prevalência e alterações clínico-laboratoriais de erliquiose, babesiose, anaplasmose, hepatozoonose e leishmania visceral caninas - Cinthya Brillante Cardinot (2017)
Five separate studies were conducted. The objective of this study was to determine the prevalence of Anaplasma platys, Babesia canis vogeli, Ehrlichia canis and Hepatozoon canis in naturally infected dogs in rural and urban areas of Alegre, Southern Espírito Santo and to verify the presence of risk factors associated with these infections. The objective of this study was to demonstrate the presence of canine visceral leishmaniasis using the enzyme-linked immunosorbent assay (ELISA) and rapid immunochromatographic test, as well as to verify the occurrence of possible cross-reactions or coinfections with different hemoparasites present in the same region. Study 3 evaluated the clinical, hematological and biochemical changes of dogs with different haemolytic diseases and compared the different infectious profiles and the influence of doxycycline treatment. Study 4 evaluated the renal alterations of dogs infected with different hemoparasites by means of renal biomarkers before and after doxycycline treatment. Study 5 evaluated the presence of thyroid hormonal changes in dogs infected with Ehrlichia canis and coinfected with Anaplasma platys and/or Babesia canis vogeli before and after treatment with doxycycline hydrochloride. In the first study, the existence of Anaplasma sp., Babesia canis vogeli and Hepatozoon canis, in the southern region of Espírito Santo and Ehrlichia canis in the same area was analyzed for the first time, and that the risk factors evaluated were In dogs with hepatozoonosis but could not be associated with Anaplasma sp., Babesia canis vogeli and Hepatozoon canis and Ehrlichia canis due to the small number of positive dogs and it is concluded that the city of Alegre is an endemic area for Hepatozoon canis, occurring in 55% of dogs evaluated. The prevalence of Anaplasma sp.,was 2%, Babesia canis vogeli was 6%, and Ehrlichia canis was 4%. In the study 2, it was concluded that in the region studied there are no autochthonous cases of dogs infected with Leishmania infantum chagasi and allowed to affirm the occurrence of cross-reactions in the ELISA test with crude Leishmania infantum chagasi antigen with hemoparasites Hepatozoon canis, Babesia canis vogeli and Ehrlichia canis. In study 3, it was concluded that the municipality studied could be considered endemic for hemoparasitoses, with autochthonous cases, and a high rate of reinfection, where co-infections are frequent and present clinical and laboratorial manifestations more intense than in monoinfected dogs. Treatment with doxycycline was effective for the clinical and laboratory improvement of dogs monoinfected with Ehrlichia canis. However, it was not effective to negatively affect dogs with babesiosis and anaplasmosis, but it did help in the clinical and laboratory improvement of infected dogs. In study 4, it was concluded that, in general, there was an increase in all the parameters evaluated in the urine of dogs that formed the experimental groups, before the treatment, and these showed a significant improvement of these variables after the end of the use of doxycycline, regardless of the negativity of the infection by hemoparasites. In the study 5, it was concluded that dogs that had Ehrlichia canis infection, monoinfected or coinfected with Babesia canis vogeli and / or Anaplasma platys, may develop diseased euthyroid syndrome due to a change in the hormonal profile during infection with hemoparasites.